Optimization of the fermentation conditions of musts from Pedro Ximenez grapes grown in Southern Spain. Production of higher alcohols and esters - Moreno, J.; Medina, M.; Garcia, M.D. (South African Journal of Enology and Viticulture, 2017)
Musts from Vitis vinifera Pedro Ximenez grapes with sugar contents of 191, 241, 300 and 342 g/l were fermented at controlled temperatures of 15, 20, 25 and 30°C. The fraction of higher alcohols and esters was determined by GLC in a capillary column. By variance analysis significant differences (p 0,01) were obtained in the production of isoamyl alcohols and 2-phenylethanol at the different fermentation temperatures, while the hexanol-1 content was found to depend on the degree of ripeness of the grapes. Only the contents in 2-phenylethyl acetate and ethyl octanoate among the esters assayed were found to depend significantly on the fermentation temperature, and only that of hexyl acetate was found to depend on the degree of ripeness (p 0,01). Taking into account the production of ethanol, higher alcohols and esters, the best results were obtained at fermentation temperatures between 20° and 25°C, for both white table wines (12% v/v ethanol) and sherry type fine wines (15% v/v ethanol).